The Quality Test for Postoperative Pain Management using the American Pain Society Patient Outcome Questionnaire Revisied (APS-POQ-R) version Indonesia at Mohammad Hoesin Hospital in Palembang (A study of the quality level of postoperative pain management - Malina Resta Maria Panjaitan; Dewi Arsinta; Rose Mafiana (Jurnal RSMH Palembang, 2020)
A B S T R A C TPain is an unpleasant sensory and emotional experience associated with actual orpotential tissue damage, or described in terms of such damage. APS-POQ-R (RevisedAmerican Pain Society Patient Outcome Questionnaire) is a measuring tool for assessingthe quality of postoperative pain management by exploring patient experiences andoutcomes. This research aims to assess the quality of postoperative pain managementat Mohammad Hoesin Hospital Palembang and to determine the factors that influenceit. The Cross-sectional observational analytic study was conducted toward 51respondents. Data was collected primarily by using questionnares and interview. Datawas analyzed by using chi-square. The study showed that the quality of postoperativepain management at RSUP Mohammad Hoesin General Hospital Palembang has goodquality with a total of 27 patients (52.9%). From statistical analysis there wassignificant relationship between the quality of post-operative pain management withage (p=0,037), gender (p=0,027), ethnicity (p=0,039), education level (p=0,039), andeconomic level (p=0,005). So it can be concluded that was a significant relationshipbetween the quality of post-operative pain management with age, gender, ethnicity,education level, and economic level.